Ekstraksi Silika Gel dari Ampas Tebu dan Sekam Padi dengan Variasi Konsentrasi NaOH dan Rasio Bahan Baku - Sania, Rasty; Anerasari Meidinariasty; Cindi Ramayanti (Jurnal Serambi Engineering, 2026)
The growing demand for environmentally friendly and sustainable materials has encouraged the exploration of agricultural waste as an alternative source of silica gel. Conventional silica gel production relies on quartz sand, which is non-renewable and requires high energy consumption. In this study, sugarcane bagasse ash and rice husk ash were utilized as potential raw materials due to their high silica content. The objective was to examine the influence of different raw material ratios and NaOH concentrations on the characteristics of the synthesized silica gel. The synthesis process involved calcination at 700°C for 4 hours, alkaline extraction using NaOH solutions (1.5 M, 2 M, and 2.5 M), and precipitation with H₂SO₄ (0.5 M), followed by drying at 110°C. The obtained silica gel was characterized for moisture content, water adsorption capacity, pH, and functional groups using FTIR spectroscopy. FTIR analysis revealed the presence of siloxane (Si–O–Si) and silanol (Si–OH) groups, confirming the successful formation of silica gel. The optimal composition was achieved at a ratio of 75% rice husk to 25% sugarcane bagasse with 2.5 M NaOH, resulting in the lowest moisture content (0.07%) and the highest water adsorption capacity (41%). These findings demonstrate that the high silica content in rice husk and appropriate alkali concentration enhance gel structure formation and improve adsorption performance.